2012
DOI: 10.1159/000341470
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Dupuytren’s Disease Cells: The Profibrogenic Role of the TGF-� Inducible p38 MAPK Pathway

Abstract: Background: Dupuytren’s disease (DD) is a nodular palmar fibromatosis that causes irreversible permanent contracture of fingers and results in the loss of hand function. Surgery still remains the only available solution for DD patients but cannot permanently cure the disease nor reduce high recurrence rates. With this rationale, we designed a study aimed at an improved understanding of the molecular mechanisms underlying DD. Our major focus was an analysis of the global gene expression profile and signalling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 73 publications
(70 reference statements)
5
14
0
Order By: Relevance
“…This study confirmed that DDC tissues had increased extracellular matrix (ECM) deposition as compared to NPF and NFF, as previously suggested by Rehman and cols [30] and by Ratkaj and cols [28]. In this sense, one of the most important ECM components is the fibrillar component, which typically becomes very abundant in Dupuytren's disease [11], [21], [31], and a major biochemical abnormality found in Dupuytren's tissue is an increase in total collagen associated with an increase in the ratio of type III to type I collagen [21].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study confirmed that DDC tissues had increased extracellular matrix (ECM) deposition as compared to NPF and NFF, as previously suggested by Rehman and cols [30] and by Ratkaj and cols [28]. In this sense, one of the most important ECM components is the fibrillar component, which typically becomes very abundant in Dupuytren's disease [11], [21], [31], and a major biochemical abnormality found in Dupuytren's tissue is an increase in total collagen associated with an increase in the ratio of type III to type I collagen [21].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, collagens types V and XIV play a role in regulating fibrillogenesis by controlling the initiation of collagen fibril assembly [35], [36]. The significant alteration of both collagens that we found in DDC tissues points to the idea that the complex process of collagen fibrils formation is disregulated in Dupuytren's disease, as previously suggested [28], [30]. Beside this, our analysis of non-fibrillar collagens such as collagens types IV, VI, VII, VIII and X revealed a significant alteration of these collagens as well, suggesting that the diffuse tissue collagen network of normal connective tissues could also be altered in DDC and NPF.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This change in gene expression patterns may be mediated by alterations of TGF- β 1-dependent signaling cascades; fibrogenic gene expression and myofibroblast conversion in fibroblasts are reportedly mediated by Smad and p38 MAPK cascades activated by TGF- β 1. 9,33,35–37 The expression of TRPA1 is upregulated in the cells with exposure to TGF- β 1, suggesting the presence of positive feedback through a TGF- β 1-induced activation of signaling cascades mediated by TRPA1. A previous report indicated that the TRPA1 receptor participates in tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have compared expression levels in primary fibroblasts derived from the affected and unaffected regions of DD patients [49] or from the two patient types [37], [43]. One compared the tissue between DD patients and hand trauma patients [30].…”
Section: Discussionmentioning
confidence: 99%